CHARACTERISTICS OF HUMIC ACIDS OF WEST-SIBERIA PEATS - L. I. Inisheva; T. V. Lasukova; G. V. Larina (Вестник Кемеровского государственного университета, 2014)
The paper aims at characterizing the humic acids (HA) of representative peats, selected by V. N. Efimova and M. G. Vasilkova’s method. The botanical composition of the Tomsk region peats is given. On the basis of elemental analysis, 13C-NMR, EPR and infra-red spectroscopy of HA the features of their structures are revealed. As a result, the possibilities of their use are evaluated.